Investigation of end effects in linear induction motors by using the finite-element method - Selcuk, A. H.; Kueruem, Hasan (Ieee-Inst Electrical Electronics Engineers Inc, 2008)
In rotating machines, no end effects occur because of their cylindrical geometry, which has no ends in the direction of movement. In linear motors, however, either the rotor or the stator has a finite length, and end effects occur because of the part having finite length entering or exiting the magnetic field. End effects occur as magnetic waves having attenuation, and play a major role in the performance of linear induction motors (LIMs), especially at high speeds. As the speed increases, efficiency decreases because of longitudinal end effects. This decrease in efficiency has a braking effect. In high-speed maglev devices, such as trains, the efficiency and performance of the LIMs become very important. We report on our investigation of end effects by the finite-element method.
Keywords: end effects; finite-element method; linear induction motor